Financial incentives for Covid-19 vaccination. A bioethical approach - Fytrou, Paraskevi (Bioethica, 2022)
The enactment of financial incentives concerning the vaccination against Covid-19 as a method to persuade the unvaccined population all over the world, raises the bioethical concern about the agreement of the measure with the basic bioethical principles as well with its moral basis. In this paper primarily, arguments about the undermining of the principle of autonomy are introduced, as the measure might be considered as an external pressure or indirect coercion which manipulates individual concern and erodes free conscious choice. At the same time, due to it, issues of exploitation and lack of respect of the subjects arise, while its compatibility with the principle of beneficence in a broad meaning, on the one hand, is redoubted, -by focusing on its moral as well as its social precarious- and the principle of juctice on the other hand, as it digs up matters of inequity and discriminatory behavior. The study of the measure’s compatibility with the above principles, is related to its moral evaluation which ends up characterizing it morally controversial, as it remotes the subject from the moral background of the useful act of vaccination. Furthermore, the measure’s utility and effectiveness are doubted, hence the measure’s espousal is considered to be intolerable in the context of the pandemic prevention, while at the same time the activation of other processes, more relevant to the bioethical principles and the respect of human dignity, is suggested.